Development of an augmented reality-based chemical bonding module assisted by the assemblr EDU - Fransisca Ditawati Nur Pamenang; Agnesia Nina Utami (Jurnal Pendidikan Kimia, 2024)
Conventional media, like textbooks, lack interaction explaining chemical bonding, hindering dynamic learning. They're static and unable to visualize bonding effectively. Moreover, unengaging teaching methods cause student disinterest, hindering learning, particularly in complex subjects like chemical bonding. To address this issue, developing augmented reality-based chemical bonding modules is a potential solution to help students learn about chemical bonding. This study aims to accomplish the following objectives: (1) Develop a chemical bonding module based on augmented reality using the Assemblr EDU, following the ADDIE development model. (2) Determine the feasibility of the augmented reality-based chemical bonding module. The research methodology employed in this study is Research and Development (R&D), utilizing the ADDIE development model. The study's findings reveal the following: (1) The module was developed using the ADDIE development model with the Assemblr EDU. (2) The augmented reality-based chemical bonding module is highly valid, achieving a material validity score of 89.33% and a media validity score of 93.5%. It is also convenient, earning an average practicality rating of 88.14% with an "excellent" response from users. Additionally, the module is effective, as evidenced by a student evaluation score averaging 70, which falls within the high criteria range. The augmented reality-based module is a valuable tool for enhancing the understanding of chemical bonding during learning.